Imaging of pediatric foot disorders - Reginelli, Alfonso; Russo, Anna; Turrizziani, Fabrizio; Picascia, Roberto; Micheletti, Elisa; Galeazzi, Vittoria; Russo, Umberto; Sica, Assunta; Cioce, Fabrizio; Aliprandi, Alberto; Giovagnoni, Andrea; Cappabianca, Salvatore (Acta Biomedica Atenei Parmensis, 2018)
Infants and children undergo imaging studies to evaluate a wide variety of congenital and acquired disorders. Imaging protocols have to consider the patient’s comfort, level of anxiety, and smaller size. The first imaging study is usually made with plain radiographs. The routine radiographic examination of the foot includes the anteroposterior (AP), lateral, and oblique projections. Magnetic Resonance Imaging (RMI) provides excellent anatomic detail of cartilage, vasculature and soft tissue thanks to superior soft tissue contrast and spatial resolution, so is valuable in many cases. According to the clinical and objective signs, guided by the radiographs images, we can be oriented to perform Computed Tomography (CT), CT imaging or MRI imaging. CT imaging is useful to observe the bones but it has the disadvantage of using radiation and doesn’t  adequately define the bone’s non-ossified portions. On the contrary, MRI imaging is very useful in identifying the cartilaginous parts and vascular and soft tissues, thanks to its superior contrast and spatial resolution. Finally, it is important to orientate the diagnostic process keeping in mind the clinical sign of the patient and to use the most appropriate diagnostic technique.